The unintended consequences of quantifying quality: does ranking school performance shape the geographical concentration of advantage? - MacArthur, D; Reeves, A (University of Chicago Press, 2022)
In this article we investigate whether quantifying school performance can have the unintended consequence of increasing the spatial concentration of advantage. Combining research on residential segregation with the sociology of quantification, we argue that ranking school performance may induce affluent parents to sort into areas with higher-ranked schools. We explore this hypothesis by analyzing linked decennial census data from 1981 to 2011 to examine whether the introduction of league tables measuring school performance in the early 1990s in England affected the spatial concentration of advantage. We find that the introduction of league tables was associated with an increase in the geographical concentration of occupational class. Advantaged households containing children became more likely to move to areas with better-performing schools after the introduction of league tables compared to less advantaged households. Quantifying school quality has the unintended consequence of increasing the geographical concentration of advantage, potentially entrenching inequalities.